(untitled) (Progressive Agriculture, 2013)
Experiments were conducted maintaining under aquarium and pond conditions using feed containing medicinal plants/extracts was evaluated on artificially and naturally infected fish with bacterial pathogens. When the fish were exposed to high bacterial pathogens Aeromonas hydrophila Ah-11, Pseudomonas fluorescens Pf-13 and Edwardsiella tarda Et-70, recovery of the infected fish varied with the pathogens challenged and feed treatments. Fish feed containing bulb extract of Allium sativum (3% feeding) showed significantly (p<0.01) high therapeutic effect recovering the infected fish (Thai silver barb, Barbodes gonionotus) with A. hydrophila (100 ± 0% recovery) and P. fluorescens (90±0% recovery). A similar result was observed in the case of pangas fish feed containing decoction of leaves of Calotropis gigantea where 100 ± 0% E. tarda infected Thai pangas (Pangasius hypophthalmus) were found to be cured. These two types of herbal feed offered similar result when applied to the naturally ulcer-affected Thai silver barb and Thai pangas fingerling under aquarium condition. In pond condition, the herbal feed containing bulb extract of A. sativum was applied experimentally to A. hydrophila infected different fish species maintained in different individual ponds where, 91.67 ± 2.35% Thai silver barb, 84.99 ± 2.35% Rui (Labeo rohita) and 74.99 ± 2.35% Mrigal (Cirrhinus cirrhosus) were found to be recovered. In contrast, plants mixed pangas feed containing decoction of leaves of C. gigantea was cured 94.44 ± 3.84% E. tarda infected Thai pangas. The other medicinal plants used in this study showed medium to weak effect recovering the bacterial infected fish. DOI: http://dx.doi.org/10.3329/pa.v19i2.16956 Progress. Agric. 19(2): 151 - 159, 2008